2016
DOI: 10.1007/s00464-016-4788-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of staging laparoscopy for detecting metastasized or locally advanced perihilar cholangiocarcinoma: a systematic review and meta-analysis

Abstract: BackgroundDespite extensive preoperative staging, still almost half of patients with potentially resectable perihilar cholangiocarcinoma (PHC) have locally advanced or metastasized disease upon exploratory laparotomy. The value of routine staging laparoscopy (SL) in these patients remains unclear with varying results reported in the literature. The aim of the present systematic review was to provide an overview of studies on SL in PHC and to define its current role in preoperative staging.MethodsA systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Up to 65–80% of patients have initially unresectable disease due to extensive hepatic artery and/or portal vein infiltration by tumor or distant metastases at time of presentation [ 10 13 ]. Of all patients who in time undergo a laparotomy, 40–70% ultimately have resectable disease [ 14 16 ]. Patients face many obstacles during diagnosis and work-up for extended resection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 65–80% of patients have initially unresectable disease due to extensive hepatic artery and/or portal vein infiltration by tumor or distant metastases at time of presentation [ 10 13 ]. Of all patients who in time undergo a laparotomy, 40–70% ultimately have resectable disease [ 14 16 ]. Patients face many obstacles during diagnosis and work-up for extended resection.…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors associated with resectability, prognosis and prediction of long and short-term survival after resection of PHC [ 15 , 76 79 ] . The most commonly used staging systems include the American Joint Committee on Cancer (AJCC) staging system with incorporated TNM classification, the Bismuth-Corlette system, the Blumgart T-staging system (MSKCC classification) and a classification recently proposed by the International Cholangiocarcinoma Group for the staging of PHC [ 14 , 15 , 20 , 77 , 79 81 ]. The AJCC staging system is based on pathology assessment of the resection specimen and is mainly used postoperatively as a prognostic tool.…”
Section: Introductionmentioning
confidence: 99%
“…LUS may theoretically be useful in detecting non-superficial liver metastases or vascular involvement, but obtaining histological evidence in the latter case might be difficult without exploration of the liver hilum. Unfortunately, limited data on the additional value of LUS are available from other studies in the literature 4. In only two of six studies, the diagnostic yield of SL was increased with the use of LUS, mainly due to the identification of locally advanced tumors 16,19…”
Section: Discussionmentioning
confidence: 99%
“…Staging laparoscopy (SL) in addition to imaging prior to exploratory laparotomy may detect small liver metastases or peritoneal metastases, thereby avoiding unnecessary laparotomy. However, the true additional diagnostic value of this procedure remains unclear, with varying results reported in the literature 4. Currently, the routine use of SL in preoperative staging of PHC is being questioned as the majority of studies from recent years have shown a diagnostic yield below 20 % and a sensitivity to detect unresectable disease lower than 60 % 59…”
mentioning
confidence: 99%
“…Coelen et al. addressed this issue in a pooled meta-analysis of 12 studies published in 2016, suggesting that 25% of patients with potentially resectable pCCA benefit from staging laparoscopy with the highest sensitivity for peritoneal metastases [ 28 ]. They suggest that with further improvement of radiological techniques through time, it may be possible to identify patients who will benefit most from laparoscopy.…”
Section: Staging Laparoscopymentioning
confidence: 99%